Rejoinder to Davidson on the Ethics of Loan Maturity Mismatching and Fractional Reserve Banking - Block, Walter E.; Barnett, William (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
Davidson (2014) takes the position that there is nothing unethical about loan maturity mismatching, particularly when a bank borrows money for a shorter time horizon than when it lends it out. The present paper takes issue with her position, and maintains that not only is this practice unethical, it should be outlawed.